The impact of using electronic applications on controlling the course of diabetes - Konaszczuk, Adrian; Bochenek, Oliwia; Koper, Mateusz; Nowak, Aleksandra; Kałuża, Jessica; Ratyna, Klaudia; Kozyra, Oliwia; Szypuła, Zofia; Paluch, Katarzyna; Skarbek, Małgorzata (Quality in Sport, 2024)
Physical activity is a fundamental element in managing diabetes. In preventing complications of this condition, along with pharmacological treatment, key factors include an appropriate diet, sports, weight reduction, and the ability to cope with stress. In recent years, the use of mobile applications in the treatment of diabetes has gained significant importance. Research has shown that these applications play a crucial role in improving patients' daily lives by offering features that make it easier to control this disease, such as advice on healthy eating, monitoring physical activity (including adjusting appropriate workouts), and assessing sleep quality and recovery. This review discusses the current research on the impact of electronic applications used in various aspects of life on health-promoting behaviors and their effectiveness in patients with diabetes. In summary, studies indicate that the use of these applications often helps participants maintain better self-control and increase self-awareness of the disease. The results of the studies also encourage further development and improvement of new possibilities made possible by the use of electronic applications. Further studies focusing on this topic are also recommended to validate the conclusions and gain new knowledge in this area.